Watershed Improvement Review Board Calendar Year 2006 Annual Report, January 31, 2007 - Simtowe, F; Muange, Elijah (My University, 2007)
The Iowa Watershed Improvement Review Board (WIRB) was created by the Iowa Legislature and signed into law by the Governor in 2005 as Senate File 200. This statute is now codified in Iowa Code Chapter 466A. The fifteen-member Board conducted eight meetings throughout the year in-person or via teleconference. Meetings were held January 22, April 23, May 17, July 17, August 13, September 24, October 29, and December 17. Attachment 3 lists the board members and their organization affiliation. The Board appointed a five-member subcommittee to review and revise the Request For Applications (RFA) documents and submit recommendations to the full Board. The RFA documents were approved as modified at the May 17, 2007 Board meeting. The Board announced the third RFA for the Watershed Improvement Fund on June 6, 2007 and accepted applications until August 1, 2007. The Board received 25 applications in response to the RFA. These applications requested $7.6 million in Watershed Improvement Funds and leveraged an additional $11.2 million for a total of $18.8 million of watershed project activity proposed. On September 24, after reviewing and ranking the applications individually, the Board met and selected ten applications for funding. The ten projects were approved for $2,656,842 of Watershed Improvement Funds. Data on the ten selected projects in 2007 include the following: •These projects included portions of 16 counties •The $2.7 million requested of Watershed Improvement Funds leveraged an additional $4.7 million for a total of $7.4 million. •Selected individual projects ranged from $42,000 to $500,000. Attachment 1 lists the calendar year 2007 approved projects name, applicant name, the water quality impairment(s) being addressed, county or counties where located, and funding amount. With funds remaining unobligated from the May 2007 RFA, a second RFA was announced November 7, 2007. This RFA will close February 22, 2008. In cooperation with the Treasurer of State, submitted the Fiscal Year 2006 report for the Tobacco Settlement Trust Fund to the Joint Transportation, Infrastructure and Capitals Appropriation Subcommittee, the Legislative Services Agency, the Department of Management and the Legislative Capital Projects Committee of the Legislative Council. Attachment 2 showing the locations of applications received during the RFAs in 2005, 2006 and 2007 and the applications selected for funding. After three RFAs, 43 projects have been funded of 111 applications. Attachment 4 contains the annual progress reports from the thirty-three projects in-progress in 2007. -1-
Keywords: Watreshed